Characterisation of the surface lewis acid/base properties of poly(butylene terephthalate) by inverse gas chromatography - Santos, José M.R.C.A. (2013)
The surface of poly(butylene terephthalate) (PBT) was analysed by means of inverse gas chromatography (IGC). The specific component of the adsorption of polar probes on the surface of poly(butylene terephthalate) was found to be endothermic, and the change in the entropy of the system, positive, which is not a common case in IGC. An interpretation is given, based on the contribution of cleavage of hydrogen bonds in the PBT and formation of hydrogen bonds between the probe-molecules and the polymer. The surface Lewis acidity and basicity constants, K and K , respectively, were a b determined and found to correlate well with an analysis of the repeating unit and end-groups in this polymer.